Implementing of 5s rule in iron-steel industry company - Horuz, Deniz; Çörekçioğlu, Selim; Raskovski, Stefan (Studia Mundi – Economica, 2021)
Nowadays, every company cares about reducing their waste and cost. While they are doing that they would prefer to make it effectively and efficiently. That is why the 5S rule is recently a more suitable tool to use for companies. In this paper, It was studied how to implement the 5S rule in an iron-steel industry company with an interview of a quality engineer who works in this company. This case study was made to be an example for the sector by photographing the before-after situations of 5S implementation. Which is carried out in the equipment and manufacturing departments of the iron-steel factory that is operating in Hatay. At the end of the 5s implementation, we may say that the risks, that may occur in the factory, are reduced, It helped to save much more time in production, and also the sustainability of the waste products has been formed to use for future needs in the factory.